Epilepsia Partialis Continua as a Sequelae of Measles Infection in Children With Hematolymphoid Malignancies - Sudivya Sharma; Chetan Dhamne; Shilpushp Bhosale; Badira Parambil; Jigeeshu Divatia; Girish Chinnaswamy; Vasundhara Patil; Rishikesh Joshi; Sridhar Epari; Anita Mahadevan; Sunil Vaidya; Shilpa Kulkarni; et al. (JCO Global Oncology, 2024)
PURPOSETo share our clinical experience with the diagnosis and management of children with hematolymphoid malignancies presenting with epilepsia partialis continua (EPC) as a sequelae of measles infection.MATERIALS AND METHODSIn December 2022, a series of children in our hemato-oncology unit presented with focal status epilepticus with no conclusive evidence pointing toward any underlying etiology. One such child had a typical measles rash a few weeks before the onset of this focal status epilepticus. After a series of cases with a similar presentation, a clinical pattern suspicious for measles became evident. cerebrospinal fluid polymerase chain reaction was positive for measles virus with measles immunoglobin M detected in the serum. This led to the diagnosis of measles inclusion-body encephalitis in a series of children who presented with EPC over a period of 3 months. EPC is a rare manifestation of measles that is seen only in immunocompromised patients.RESULTSAmong the 18 children reported in this series, only 10 had a history of rashes. The rash was mostly transient and elicited only on retrospective history taking. Five of the 18 children who did not lose consciousness during the prolonged seizure episode survived the disease but had residual neurologic sequelae. Among the 18 children, two were unimmunized and immunization status could not be confirmed in three other children.CONCLUSIONThis case series highlights the threats posed by measles infection in children with cancer who are immunosuppressed because of the underlying disease and ongoing chemotherapy. Loss of herd immunity because of declining measles immunization rates secondary to vaccine hesitancy and COVID-19 lockdown pose a greater risk of measles infection and its complications for patients with deficient immune systems.